The Impact of Digital Stress on The Hypothalamic-Pituitary-Ovarian Axis and Menstrual Cycle – A Systematic Review with Implications of Digital Health Technologies - Zatyka, Antonina; Krupski, Aleksander; Marusza, Michal; Stielow, Victoria (Quality in Sport, 2026)
The growing use of digital technology has created a new form of chronic psychological stress. Digital stress significantly affects female hormonal and reproductive health. This systematic review explores how digital and lifestyle related stress affects the hypothalamic-pituitary-adrenal (HPA) axis. It also examines the HPA and hypothalamic-pituitary-ovarian (HPO) axes relationship, specifically how it influences menstrual cycle regulation. A comprehensive literature search was performed using PubMed-indexed studies from January 2022 through March 2026 to identify relevant studies on all aspects of stress, neuroendocrinology, and menstrual health. These results indicate that chronic stress causes prolonged activation of the HPA axis resulting in increased cortisol levels and disrupts the negative feedback loops of hormones that are normally involved in the regulation of the menstrual cycle. This disruption prevents normal secretion of Gonadotrophin releasing hormone (GnRH) which disrupts Luteinising Hormone (LH) and Follicle Stimulating Hormone (FSH) activity which contributes to menstrual disorders or anovulatory cycles. There is emerging data suggesting that certain types of digital stressors such as excessive screen time, social media or sleep disturbance may contribute to these outcomes by creating chronic stress states and circadian disruptions. Despite providing new avenues for identifying menstrual and stress related fluctuations through digital health technologies, there continue to be limitations and validations required for these tools. Collectively, the review demonstrates a complex interplay among modern lifestyle characteristics and endocrine regulation supporting continued investigation into the role of digital stress in women's reproductive health.